TRADISI SEBAGAI MEDIA KOMUNIKASI - Yan Anugrah Wisesa; I Putu Mardika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Implementation of tradition in the community did not escape from the role of communication in it that can provide convenience for people to interact in their participation as individuals directly involved in it. Communication is a process of forming, delivering, receiving, and processing messages that occur within a person and between two or more persons with a particular purpose. Each communication must have a purpose of communication, one of the objectives is to transfer the value of norms, customs or culture of a region. With the advancement of science and technology that is increasingly global today, tradition exemplifies the role of communication in order to remain keep wholeness and holies. On this good occasion the author as the next generation discusses the role of communication in the implementation of tradition. The purpose of this study is to understand and study the relationship of tradition and communication in an effort to create togetherness and deep understanding of the meaning to implementation of tradition as a guide for community life in the current era of globalization. The results found : (1) The most basic of the tradition is the information passed on from generation to generation both written and oral, because without this a tradition can become extinct. Tradition is a custom, a culture that is a habit that continues on an ongoing basis and will continue to be done by the next generation either individual or group. Implementation of a tradition in the Hindu’s community in Bali is generally related to the concept of Tri Hita Karana is to seek a harmonious relationship between God with humans, humans with humans and humans with the environment. (2) With the development of communication technology, the interaction that occurs today makes it easier for mankind to fulfill information through various effective and efficient media. In the study of its forms, communication is generally divided into verbal and non-verbal forms. (3) Human interaction generally always have functions and goals that are beneficial to the development of life and the development of self potential to be able to provide positive things for the surrounding community. Interaction in the form of communication in general has a function and purpose depends on where the communication is carried out or when the communication took place. Keywords: Tradition, Communication Media